Osservazioni su Bambini e Anziani: tra continuità storiche e inedite prospettive educative - Di Sandro, Elena (Studi sulla Formazione/Open Journal of Education, 2018)
The article deals both with Childhood and Seniority. In particular, it examines the current considerations about these two different life’s seasons, analyzing the most important pedagogical studies about them and the latest international documents and recommendations. The myth of childhood, the active ageing and the lifelong learning perspective are some of the instance the article refers to, focusing also to the grandparenting as an opportunity to interpret the seniority in a new way.